Response Inhibition and Interference Control in Obsessive–Compulsive Spectrum Disorders - van Velzen, Laura S.; Vriend, Chris; de Wit, Stella J.; van den Heuvel, Odile A. (Frontiers in Human Neuroscience, 2014)
Over the past twenty years, motor response inhibition and interference control have received considerable scientific effort and attention, due to their important role in behavior and the development of neuropsychiatric disorders. Results of neuroimaging studies indicate that motor response inhibition and interference control are dependent on cortical-striatal-thalamic-cortical (CSTC) circuits. Structural and functional abnormalities within the CSTC circuits have been reported for many neuropsychiatric disorders, including obsessive-compulsive disorder (OCD) and related disorders, such as attention deficit hyperactivity disorder (ADHD), Tourette’s syndrome (TS) and trichotillomania. These disorders also share impairments in motor response inhibition and interference control, which may underlie some of their behavioral and cognitive symptoms. Results of task-related neuroimaging studies on inhibitory functions in these disorders show that impaired task performance is related to altered recruitment of the CSTC circuits. Previous research has shown that inhibitory performance is dependent upon dopamine, noradrenaline and serotonin signaling, neurotransmitters that have been implicated in the pathophysiology of these disorders. In this review we discuss the common and disorder-specific pathophysiological mechanisms of inhibition-related dysfunction in OCD and related disorders.